Perancangan Buku Ilustrasi “Nyanyian Anak Balam Rabab Pasisia“ - Adha Zuhkri Arafad; Budiwirman Budiwirman (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The Balam Rabab Pasisia Children's Song is a folk tale from the Minangkabau people, West Sumatra, South Coast. It is said that the children's singing of Balam is a traditional healing process. In the past, someone from the family who was sick would be taken to a shaman (smart person) to carry out a healing ritual. In line with the development of the Balam Children's Song era, it has now entered the Pesisian rabab performing arts. Besides that, rabab is a performing art that tells stories about kaba from other folk tales. This is what prompted the designer to design the illustrated book ''Nyaniyan Anak Balam Rabab Pasisia''. There are still many among the younger generation who do not know the culture, traditions and folklore because there is a lack of information and dissemination is still not effective. The aim of designing the illustration book